The Lighthouse Campus: Guiding the Future of Education Through Intelligent Connection and Seamless Innovation - Anasuya Vemuri (Journal of Computer Science and Technology Studies, 2025)
This article examines the transformative impact of digital technologies on higher education through the concept of the "Lighthouse Campus" – an intelligent, connected ecosystem that leverages artificial intelligence, cloud computing, and no-code platforms. The article explores how these integrated technologies are revolutionizing institutional operations, personalizing learning experiences, and democratizing digital innovation in educational settings. Through analysis of recent implementations across multiple institutions, the article demonstrates significant improvements in student engagement, administrative efficiency, and research productivity. The article highlights how automated workflows, AI-driven personalization, and no-code solutions are enabling educational institutions to enhance student success, streamline operations, and foster innovation while reducing technological barriers and operational costs.